Alumni feedback: areas for improvement in the teaching of English for occupational purposes / Nuraihan Mat Daud, Nurul Syafieqah Jaafar and Nor Shidrah Mat Daud - Mat Daud, Nuraihan; Jaafar, Nurul Syafieqah; Mat Daud, Nor Shidrah (Akademi Pengajian Bahasa, 2019)
Alumni feedback is an important means of determining whether a course is of relevance to the students’ needs. One of the courses that would benefit from their feedback is English for Occupational Purposes. Based on the practice at the workplace, graduates can provide information whether what was taught could be applied to their working environment. This study seeks to ascertain whether an EOP course is relevant to the needs of the graduates. A questionnaire survey was conducted, and a total of thirty alumni of an Arts Faculty of a public university in Malaysia responded to the survey. The findings indicate that the students benefited from the course, but a number of improvements could be made to make the course more effective. The study also highlighted the varieties of language used at work.